Implementation of the Kauny Quantum Memory Method in Improving the Ability to Memorize and Understand the Qur'an (Multi-Site Study at SD Islam Imam Syafi'i Kisaran and SDS IT Ar-Roja Kisaran) - Utari, Anggie Sri; Sinaga, Ali Imran; Haidir, Haidir (FKIP-Universitas Riau, 2025)
This study aims to analyze the implementation of the Kauny Quantum Memory method in improving the ability to memorize and understand the Qur'an at SD Islam Imam Syafi'i Kisaran and SDS IT Ar-Roja Kisaran. The Kauny Quantum Memory method emphasizes an approach based on relaxation, visualization, and memory binding techniques to make it easier for students to memorize and understand the meaning of the Qur'an. This study uses a qualitative method with a multi-site study approach. Data were collected through observation, interviews, and documentation of tahfiz teachers, students, and other related parties. The results of the study showed that the application of the Kauny Quantum Memory method had a positive impact on students' memorization and understanding. The implementation of this method is carried out through several stages, namely planning, implementation, and evaluation. This study concludes that the Kauny Quantum Memory method is effective in improving students' memorization and understanding of the Qur'an and contributes to the development of more innovative tahfiz learning methods.